If the current age of a person be X, then

- age after n years = X + n
- age n years ago = X – n
- n times the age = nX
- If ages in the numerical are mentioned in ratio A : B, then A : B will be AX and BX

Present ages of B to C = 3x - 6, 2x

Present ages of A to C = 2 : 1(2x, x)

Present ages of A, B and C = 4x, 3x - 6, 2x

B = A – 13

A – B = 13

4x – (3x - 6) = 13

4x – 3x + 6 = 13

X = 7

B’s age, after 5 years = 3x – 6 + 5 = 21 – 1 = 20 years

[latex]\Rightarrow 28 \times 3 [/latex] = 84 years

Total present ages of A, B and C = 84 + 9 = 93 years

Total present ages of A, B, C and D = 32 [latex]\times[/latex] 4 = 128 years

Present age of D = 128 – 93 = 35 years

Age of D, 8 years ago = 35 – 8 = 27 years.

The present age of A and B = 3x + 5, 2x + 5

Present age of C = Present age of A – 7

Present age of D = 35 – 6 = 29

Present age of C = 2 [latex]\times[/latex] present age of D

[latex]\Rightarrow 2 \times 29 [/latex] = 58 years

Present age of A = 58 + 7 = 65 years

3x + 5 = 65

3x = 60

X = 20

The present age of B = 2x + 5 = 45 years

Preethi’s present age = 30 years

Silambu’s present age = 30 – 5 = 25

Silambu’s age 8 years ago = 17

X = 17

2x = 34

After 7 years, the age of Kavi = 34 years

Present age of Kavi = 27 years

The present age of C = [latex]{(\frac {B’s present age}{2})}^{2}[/latex]

A’s age after 6 years = 18 years

Present age of A = 12 years

6x = 12

X = 2

Present age of B = 7x = 14 years

Present age of C = [latex]{(\frac {14}{2})}^{2} = {7}^{2}[/latex] = 49 years

© 2013 - 2023 SPLessons.com